PENGARUH MODEL PROBLEM-BASED LEARNING BERBANTUAN GEOGEBRA TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS DAN SELF-CONCEPT SISWA - Derisa Putri Andhini; Savitri Wanabuliandari; Jayanti Putri Purwaningrum (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
The purpose of this study was to determine the average difference in the ability to understand mathematical concepts of students who obtained the Geogebra-assisted Problem-Based Learning model better than students who obtained the direct learning model. This research uses a quantitative approach with quasi-experimental design methods. The research design used was the nonequivalent pretest-posttest control group design. The population in this study is all grade X students of SMA N 1 Gebog for the 2022/2023 school year with the Purposive Sampling sampling technique. The sample used is 2 classes, class X E-2 is selected as an experimental class and will be applied Problem-Based Learning model assisted by Geogebra. Meanwhile, class X E-3 as a control class will be applied direct learning model. Data analysis techniques using prerequisite tests include normality tests, homogeneity tests. The hypothesis test uses an independent samples t-test. The results showed that the average ability to understand mathematical concepts of students who obtained the Geogebra-assisted Problem-Based Learning model was better than students who obtained the direct learning model